Mild fabrication of silica-silver nanocomposites as active platforms for environmental remediation1. Issue 13 (14th February 2015) - Mignani, A.; Fazzini, S.; Ballarin, B.; Boanini, E.; Cassani, M. C.; Maccato, C.; Barreca, D.; Nanni, D.
<x xml:space="preserve">Abstract</x> A new, simple and convenient approach to prepare silver nanoparticles supported on SiO2–PEI composites for the decoloration of organic dyes.